Quality Use of Quality Medicines - Thomas, Dixon; Sundararaj, Kishore Gnana Sam; Shirwaikar, Annie; Shirwaikar, Arun (Journal of Pharmacy Practice and Community Medicine)
The use of medicines as healthcare interventions bring to the fore 2 important aspects of quality namely; ‘quality of medicines’ and ‘quality use of medicines’ (QUM). Governmental and non-governmental agencies in a regulatory and advisory role monitor medicines for quality production, distribution and proper use. Reports about substandard quality medicines suggest a need for further improvements in quality production and distribution of medicines.